Anaphylaxis to Ceftriaxone – Evaluation of Two Cases - Hirachan, Rozeeta; Gopi, PH; Bibek, R; KC, Hari; Tumaya, G; Thaneshwor, P; Sandeep, N (Journal of Gandaki Medical College-Nepal, 2018)
Allergic reactions to beta-lactamase antibiotics are the most common cause of adverse drug reactions mediated by specific immunological mechanism. Anaphylaxis is diagnosed clinically. In two of our cases, patients developed acute respiratory distress syndrome (ARDS) secondary to anaphylaxis, which was however managed successfully without residual deficits.